ANALISIS PENGARUH INTELLECTUAL CAPITAL TERHADAP MARKET VALUE DAN FINANCIAL PERFORMANCE PERUSAHAAN DENGAN METODE VALUE ADDED INTELLECTUAL COEFFICIENT - FARAH MARGARETHA; ARIEF RAKHMAN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2006)
The purpose of this research is to investigate the relation between the value creation efficiency of firms' intellectual capital and firm's market valuation and financial performance. Using 13 manufacturing companies data drawn from Jakarta Stock Exchange (JSX) reporting period 1999-2003 and Pulic's Value Added Intellectual Coefficient (VAIC) as the efficiency measure of three intellectual capital component; capital employed efficiency (VACA), human capital efficiency (VAHU), and structural capital efficiency (STVA) and multiple regression model to examine the relationship between corporate value creation efficiency and firms' market-to-book value ratio, and explore the relationship between intellectual capital and firms' financial performance. The simple regression used to examine the relationship between VAIC and market value and relationship between VAIC and financial performance. The result is not support the first model; market value hypothesis that there is significantly negative between intellectual capital and market-to-book value ratio (M/B). The second model of the regression show there are positively associated between the three of intellectual capital component and return on equity (ROE) as financial performance.